Sortase A Fusion Expression and mIFc2 Co-Expression of Bovine Lactoferricin and Analysis of Its Antibacterial Activity - Hsu, Chao-Yu; Hsieh, Chung-Yiu; Yang, Cheng-Yao; Chang, Yu-Kang; Shih, Wen-Ling; Yeh, Chuan-Ming; Hu, Nien-Jen; Chen, Ming-Shan; Nielsen, Brent L.; Liu, Hung-Jen (Processes, 2022)
The coding region for the sortase A (SrtA) of Staphylococcus aureus was fused at the N-terminus of LfcinB. The SrtA-LfcinB fusion protein in E. coli C43(DE3) was expressed with the expected sizes of 21 kDa and 38 kDa by pET21b-SrtA-LfcinB and pET32-1SrtA-LfcinB constructs, respectively. Increased levels of the TrxA-His-SrtA-SrtA-LfcinB fusion protein were detected by the pET32-3SrtA-LfcinB construct having three expression cassettes. LfcinB is released from the expressed SrtA-LfcinB protein by SrtA self-cleavage which is induced in the presence of Ca2+. The antibacterial activity was detected after SrtA-mediated cleavage of LfcinB. Furthermore, to reduce the antimicrobial peptide toxicity to the E. coli host, the human interferon-γ (hIFN-γ) sequences were mutated into a negatively charged mIFc2 protein (7 kDa), which was co-expressed with LfcinB in an insoluble form. The yield of LfcinB was elevated while changing the gene order of LfcinB and mIFc2 (pET21b-fLfcinB-bmIFc2). Furthermore, increased levels of LfcinB were detected using the pET21b-(fLfcinB-bmIFc2)2 construct. To increase the dissolution rate of inclusion bodies, inclusion bodies treated with different temperatures and pH and resuspended in different volumes of 50 mM Tris-HCl were assayed. Our results reveal that heat-treated LfcinB/mIFc2 inclusion bodies at 90 °C, pH 10, and 16X resuspended volumes have the best resolubilization rate. This work suggests that the mIFc2 co-expression system shows higher efficiency for LfcinB production than the SrtA fusion system. The expressed LfcinB from the mIFc2 co-expression system exhibits excellent broad-spectrum antibacterial activities against thirteen Gram-negative and ten Gram-positive bacteria species with a range of minimum inhibitory concentrations (MIC) between 37–150 ug/mL.